Strategi Pemasaran E-Commerce Retail Sayuraya dengan Analisis SWOT - Nurun Ni`mah (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The development of information technology is currently developing rapidly and is increasingly widespread, providing changes in ways and business processes in the trade industry. One of the businesses on the internet is called e-commerce. Sayuraya is an e-commerce platform in the grocery & retail sector that provides food needs for consumers. In running this e-commerce business, of course there are many obstacles and obstacles faced by Sayuraya, especially business competition between e-commerce. But behind everything, Sayuraya has definitely prepared a big enough business marketing strategy so that the company can survive and grow to its current stage. As an e-commerce platform, Sayuraya has a competitive advantage over its competitors, therefore this research was conducted to find out how Sayuraya's marketing strategy was carried out using SWOT analysis. This type of research is a qualitative research that seeks to collect facts and data collection is carried out by the interview method. Keywords: Marketing Strategy, E-Commerce, SWOT Analysis